Lisztharmat gombák az európai mogyorón (Corylus avellana) - Pintér, Csaba; Kövics, György; Biró, Györgyi; Csüllög, Kitti (GEORGIKON FOR AGRICULTURE, 2022)
European hazelnut (Corylus avellana) leaves infested by powdery mildews were collected in the region of Keszthely, viz. Cserszegtomaj, Keszthely, Ajka and Csabrendek in November of 2021 based on the morphological characteristics. One of the pathogens was found belonging to the genus Erysiphe ( Erysiphe sect. Microsphaera) which species has not been observed on hazelnut in Hungary yet. In addition, the casmothecia of the other common powdery mildew species, Phyllactinia guttata was also appeared on Corylus leaves at the same time. As numerous powdery mildews can be harmful on different hazelnut species worldwide, beside of the morphological characteristics, application of molecular tools are also indispensable to the proper identifications which are currently in progress at the Institute of Plant Protection of the University of Debrecen.
Keywords: Erysiphe sp.; Phyllactinia guttata; Corylus; powdery mildews of hazelnut